FINANCING PRODUCT DIVERSIFICATION STRATEGY AND ITS IMPLICATIONS FOR PROFIT-AND-LOSS SHARING FINANCING CREDIT RISK (MUDHARABAH AND MUSYARAKAH CONTRACTS) - Ahmad Syukri; Meilita Tryana Sembiring; Fahmi Natigor (PT. Radja Intercontinental Publishing, 2026)
This study investigates the effectiveness of product diversification in managing credit risk in profit-and-loss sharing (PLS) financing at Bank Sumut Syariah. While Islamic banking theoretically leverages diversification for risk mitigation, akin to Modern Portfolio Theory, this research reveals an